Peningkatan Hasil Belajar Matematika Volume Balok Dengan Kombinasi Model PBL, RME, Dan TaLKING STICK Di SD Muhammadiyah 5 Banjarmasin - Novita Sari; Susilawaty (CV. ITTC INDONESIA, 2023)
This study was motivated by the lack of students' ability to solve problems, students are less involved in the learning process, monotonous learning does not use media, concrete examples and varied models so that it has an impact on student learning outcomes. The purpose of the study was to describe teacher and student activities and analyze student learning outcomes using a combination of PBL, RME, and Talking Stick models. The research subjects were 10 students in the fifth grade of SD Muhammadiyah 5 Banjarmasin. The instruments used were teacher and student activity observation sheets, evaluation sheets. The results of the study prove that teacher activity has increased in cycle I meeting 1 reached 83%